Новая промышленная революция и глобализация современного мира - Скрипник, К. Е. (ХНУРЕ, 2021)
The article examines the problems and prospects of globalization transformations of the modern world. It is shown that with all the variety of approaches to understanding the process of globalization itself, globalization transformations affect the entire world community and require special attention. In recent decades, the world has faced an unprecedented increase in nationalism and protectionism, a slowdown in the growth of world trade and the movement of capital flows. The result of these changes has been the active formation of flexible economic mega-partnerships that which provide interaction in a limited range of areas and more rigid alliances that imply interaction of a mandatory nature.
Keywords: философия; глобализация; новая промышленная революция